Erratum to "Some characterizations of hyperbolicRicci solitons on nearly cosymplectic manifolds with respect to the Tanaka-Websterconnection" - Murat Altunbaş (Istanbul Journal of Mathematics, 2026)
In this erratum, we correct several inaccuracies and typographical errors in our paper “Some characterizations of hyperbolic Ricci solitons on nearly cosymplectic manifolds with respect to the Tanaka-Webster connection” [Istanbul J. Math. 2 (1), 28–32, 2024]. DOI: 10.26650/ijmath.2024.00012